A Simplified Method for Simultaneous Determination of α-Lipoic Acid and Low-Molecular-Mass Thiols in Human Plasma - Borowczyk, Kamila (Int J Mol Sci, 2020)
α-Lipoic acid, glutathione, cysteine, and cysteinylglycine can be applied as therapeutic agents in civilization diseases such as diabetes mellitus, cardiovascular diseases, and cancers. On the other hand, a higher concentration of homocysteine can result in health problems and has been indicated as an independent risk factor for cardiovascular disease and accelerated atherosclerosis. Here, the first simplified HPLC-UV assay that enables simultaneous determination of α-lipoic acid and low-molecular-mass thiols in plasma, reduces the number of steps, shortens the total time of sample preparation, and limits the amount of single-use polypropylene laboratory materials is described. The assay is based on reversed-phase high performance liquid chromatography with UV detection and simultaneous reduction of disulfide bound with tris(2-carboxyethyl)phosphine and the selective pre-column derivatization of the thiol group with 1-benzyl-2-chloropyridinium bromide. Linearity in the detector responses for plasma samples were observed in ranges: 0.12–5.0 nmol mL(−1) for α-lipoic acid; 2.0–20.0 nmol mL(−1) for glutathione, cysteinylglycine, and homocysteine; and 40.0–400.0 for cysteine. The LODs for α-lipoic acid and low-molecular-mass thiols were 0.08 and 0.12 nmol mL(−1), respectively, while LOQs were 0.12 and 0.16 nmol mL(−1), respectively. The usefulness of the proposed method has been proven by its application to real samples.